Clearing Amyloid-Beta by Astrocytes: The Role of Rho GTPases Signaling Pathways as Potential Therapeutic Targets - Gyeongah Park; Zhen Jin; Hui Lu; Jianyang Du (Brain Sciences)
Astrocytes, vital support cells in the central nervous system (CNS), are crucial for maintaining neuronal health. In neurodegenerative diseases such as Alzheimer’s disease (AD), astrocytes play a key role in clearing toxic amyloid-β (Aβ) peptides. Aβ, a potent neuroinflammatory trigger, stimulates astrocytes to release excessive glutamate and inflammatory factors, exacerbating neuronal dysfunction and death. Recent studies underscore the role of Rho GTPases—particularly RhoA, Rac1, and Cdc42—in regulating Aβ clearance and neuroinflammation. These key regulators of cytoskeletal dynamics and intracellular signaling pathways function independently through distinct mechanisms but may converge to modulate inflammatory responses. Their influence on astrocyte structure and function extends to regulating endothelin-converting enzyme (ECE) activity, which modulates vasoactive peptides such as endothelin-1 (ET-1). Through these processes, Rho GTPases impact vascular permeability and neuroinflammation, contributing to AD pathogenesis by affecting both Aβ clearance and cerebrovascular interactions. Understanding the interplay between Rho GTPases and the cerebrovascular system provides fresh insights into AD pathogenesis. Targeting Rho GTPase signaling pathways in astrocytes could offer a promising therapeutic approach to mitigate neuroinflammation, enhance Aβ clearance, and slow disease progression, ultimately improving cognitive outcomes in AD patients.